If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(x + 2) + x = 4 Reorder the terms: -4(2 + x) + x = 4 (2 * -4 + x * -4) + x = 4 (-8 + -4x) + x = 4 Combine like terms: -4x + x = -3x -8 + -3x = 4 Solving -8 + -3x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -3x = 4 + 8 Combine like terms: -8 + 8 = 0 0 + -3x = 4 + 8 -3x = 4 + 8 Combine like terms: 4 + 8 = 12 -3x = 12 Divide each side by '-3'. x = -4 Simplifying x = -4
| 9x+29=4x+1 | | -7=9-3n+5n | | 4x/3=18 | | (4x+7)(-7x+4)= | | -10x-4=11-7x | | -5x-4x+7=-5 | | 2x^4+18x^2+243=0 | | 5x+4x-8=1 | | 17+8-20=4(a-7)-3 | | 11-5= | | 4(2x-10)=-10(x-5) | | 3x+243=12x-9 | | 2x^4+18x^2-243=0 | | 218-2x=43x+23 | | Y=2x^2-16x+25 | | 17+2b-4c=4(a-7)-3 | | 192-6x=6x+12 | | y*12=-60 | | 7x+5-5x-2=11 | | 5a=0 | | 2x+2y+3z=3 | | 5y=13 | | -2x-5=x+7 | | -2w=-0,5 | | 4n^2-3n-13=0 | | 22(-c)=-66 | | 12-5x=2x^2 | | 33-16=8-16+5a+5 | | 12*5= | | (2x+1)(3x-8)=(5x-24)(2x-5)-192 | | 28-4a=6(2a-2)+24 | | 5x+1=2x+22 |